Carnosinase-1 knock-out reduces kidney fibrosis in type-1 diabetic mice on high fat diet - Pfeffer, Tilman; Wetzel, Charlotte; Kirschner, Philip; Bartosova, Maria; Poth, Tanja; Schwab, Constantin; Poschet, Gernot; Zemva, Johanna; Bulkescher, Ruben; Damgov, Ivan; Thiel, Christian; Garbade, Sven; et al. (Antioxidants, 2023)
Carnosine and anserine supplementation markedLy reduce diabetic nephropathy in rodents. The mode of nephroprotective action of both dipeptides in diabetes, via local protection or improved systemic glucose homeostasis, is uncertain. Global carnosinase-1 knockout mice (Cndp1-KO) and wild-type littermates (WT) on a normal diet (ND) and high fat diet (HFD) (n = 10/group), with streptozocin (STZ)-induced type-1 diabetes (n = 21-23/group), were studied for 32 weeks. Independent of diet, Cndp1-KO mice had 2- to 10-fold higher kidney anserine and carnosine concentrations than WT mice, but otherwise a similar kidney metabolome; heart, liver, muscle and serum anserine and carnosine concentrations were not different. Diabetic Cndp1-KO mice did not differ from diabetic WT mice in energy intake, body weight gain, blood glucose, HbA1c, insulin and glucose tolerance with both diets, whereas the diabetes-related increase in kidney advanced glycation end-product and 4-hydroxynonenal concentrations was prevented in the KO mice. Tubular protein accumulation was lower in diabetic ND and HFD Cndp1-KO mice, interstitial inflammation and fibrosis were lower in diabetic HFD Cndp1-KO mice compared to diabetic WT mice. Fatalities occurred later in diabetic ND Cndp1-KO mice versus WT littermates. Independent of systemic glucose homeostasis, increased kidney anserine and carnosine concentrations reduce local glycation and oxidative stress in type-1 diabetic mice, and mitigate interstitial nephropathy in type-1 diabetic mice on HFD.
Gesehen am 18.08.2023